If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 19 = 3 + -3x Reorder the terms: 19 + 5x = 3 + -3x Solving 19 + 5x = 3 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 19 + 5x + 3x = 3 + -3x + 3x Combine like terms: 5x + 3x = 8x 19 + 8x = 3 + -3x + 3x Combine like terms: -3x + 3x = 0 19 + 8x = 3 + 0 19 + 8x = 3 Add '-19' to each side of the equation. 19 + -19 + 8x = 3 + -19 Combine like terms: 19 + -19 = 0 0 + 8x = 3 + -19 8x = 3 + -19 Combine like terms: 3 + -19 = -16 8x = -16 Divide each side by '8'. x = -2 Simplifying x = -2
| 2(y+3)+10=32 | | 2x+21=5x-12 | | (4a+2y)-(4a-3y)= | | 8(5x+6)=3(4-7) | | 4y^2+12y= | | x=.08*200 | | V+6x=X+W | | x=8*200 | | 7n-3=3n+15 | | x=y-90/4 | | 6-7x=11+31x | | 5x-3y=2xy-11 | | 8a=49 | | 3x+y^2=7 | | 5/7÷5/8= | | 4/5(3x/2-5) | | 4/5(3x/2-5)(10x-2) | | 49y^2-64=0 | | 3x/15x=9 | | 4z/9-1=1 | | cos(x)=2.625 | | cosx=2.625 | | 4/5(3x/2-5)(10x-2)=0 | | 6x/36=12 | | 8x-22=64+6x | | 5(4x-3)=2(2+6) | | 5*x+7=8 | | 15w-2(w+5)=11 | | 4xp=68 | | 9x+3=7x+45 | | 7X-3=4x+10+2 | | (x+5-3i)(x+5+3i)(x-2)(x-2)= |